The earliest European Acheulean: new insights into the large shaped tools from the late Early Pleistocene site of Barranc de la Boella (Tarragona, Spain) - Ollé, Andreu; Lombao, Diego; Asryan, Lena; García-Medrano, Paula; Arroyo, Adrián; Fernández-Marchena, Juan Luis; Yeşilova, Görkem C.; Cáceres, Isabel; Huguet, Rosa; López-Polín, Lucía; Pineda, Antonio; García-Tabernero, Antonio; et al. (Frontiers in Earth Science, 2023)
Since the oldest known Acheulean lithic techno-typological features in Europe were reported at the site of Barranc de la Boella (Tarragona, Spain), continuous fieldwork has been conducted there in archeological deposits of the late Early Pleistocene age (0.99–0.78 Ma). As a result, excavations in two of the three open-air localities have significantly expanded the collection of lithic and faunal remains, allowing us to make progress in the interpretation of the hominin behaviors in an open-air fluvial-deltaic sedimentary environment. This includes examples of cumulative palimpsests, such as those found at the locality of La Mina, in which hominins only had a minimal role as modifying agents, as well as the extraordinary mammoth butchery site recorded at the Pit 1 locality. The aim of this paper is to present a comprehensive update of the collection of large shaped tools and to assess its significance in the framework of the earliest occurrence of the Acheulean in Europe. This cultural entity is increasingly well-documented for the early Middle Pleistocene, but very little is known about its presence in Europe before the Brunhes–Matuyama boundary. Large shaped tools appear in the three localities explored in the Unit II of Barranc de la Boella, including choppers (unifacial and bifacial) and standard Acheulean forms, such as picks, knives, and cleaver-like forms. Techno-typological and morphometrical analyses revealed a basic heavy-duty component obtained through simple shaping sequences coupled with significantly more elaborate tools produced on various large blanks (cobbles, slabs, or flakes). The complete bifacial and bilateral shapings have yet to be documented, but the present specific tool assemblage attests to the Early Acheulean technological threshold. Hence, the archaeological data from Barranc de la Boella provide insights into the first appearance of the Acheulean technology in Europe and add critical information to the debate on the technological variability of the Early Pleistocene hominin occupation of the continent. The results of this study revealed a technological assemblage unique in the known late Early Pleistocene archeological record from Europe, different from the rest of ancient Acheulean sites in this continent, which are dated at the Middle Pleistocene. This lends support to the hypothesis that Barranc de la Boella may represent a previously unrecognized Early Acheulean dispersion out of Africa connected to its first evidence at the gates of Eurasia, potentially moving over the northern Mediterranean coastal road to reach Western Europe.